(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
During school age, rapid physical, intellectual, mental, and social growth occurs, necessitating increased nutritional intake to support growth and activities. This coincides with the crucial issue of stunting in Indonesia. The food consumed plays a crucial role in determining the nutritional balance of school-aged children. Community Service activities with accompanying outreach are expected to provide the understanding and practical application of healthy food types to teachers and canteen operators. The method employed in this activity involves observing Elementary School Jogorogo 4 regarding data measurement and analysis of student participants, followed by outreach activities on balanced nutrition and the implementation of a healthy canteen. Thus, the nutritional needs of young children can be maintained, reducing the risk of stunting